CDApps: integrated software for experimental planning and data processing at beamline B23, Diamond Light Source. Corrigendum. (1st May 2015) - Hussain, Rohanah; Benning, Kristian; Myatt, Daniel; Javorfi, Tamas; Longo, Edoardo; Rudd, Timothy R.; Pulford, Bill; Siligardi, Giuliano
Abstract : In the paper by Hussain et al. [(2015), J. Synchrotron Rad.22, 465468 ], Daniel Myatt is missing from the list of authors. The complete list of authors should be Rohanah Hussain, Kristian Benning, Daniel Myatt, Tamas Javorfi, Edoardo Longo, Timothy R. Rudd, Bill Pulford and Giuliano Siligardi.